Dirasah Bunyawiyah Jenetikiyah fi al-Syi’ri “Shumtu Min Ajli Ghazah” Li Mahmud Darwis Inda Nadzariyah Lucien Goldman - Muhdie Karim; Jauharotul Firdaus (Arabic Language and Letters Department, 2020)
AbstractPoetry is a form of expression by a poet in describing a certain thing. It is the same with Sumtu poetry, which describes Palestine's longing for Gaza. This study aims to determine the form of the intrinsic and extrinsic elements in Mahmud Darwish's Sumtu Min Ajli Ghazah based on Goldman's perspective. This research is a descriptive qualitative study with a genetic structuralism approach. In collecting the data, the researcher applied reading and note-taking techniques. Then, they were analyzed based on the Miles and Huberman model. The results showed that the concept of human facts were the problems of misery, oppression, and human violence in Palestine. The concept of a collective subject was a representation of two large conflicting groups consisting of the Israeli Society as superior and the Gazan people as inferior. This poem's world view is to reveal the author's partiality to the Palestinian people to face Israeli oppression. Besides, the concept of understanding - explanation describes societal factors and individual factors. The social factor was also the author's concern for the social situation around him caused by humanitarian problems that never end. Meanwhile, the individual factor that appeared in the poetry reflects the author's thoughts and feelings towards humanitarian problems that never stop in his country.